Poems by Adriano de San Martin - Corrales Arias, Adriano (2025)
The poems presented constitute a sample selected by the author from his last five published books, namely Vanitas, Vigilia (Vigil), Secuencias (Sequences), Elegías de labrador (Farmer’s Elegies), and Gin Tonic. The first two poems were written during the COVID-19 pandemic and can be read as a testimony to the anguish and sorrow experienced during that fateful period. The third poem is a text that delves into the crisis of postmodernity and its discourses with disruptive language like that used in cinema. And the last two, as their names suggest, are elegiac poetry collections about the “dark night of the soul,” when love breaks down or is not enough for lovers or for humanity in general.